Geometric optimisation of thermo-electric coolers using simulated annealing - Khanh, D.V.K. (Inderscience Enterprises Ltd., 2017)
The field of thermo-electric coolers (TEC) has grown drastically in recent years. In an extreme environment such as thermal energy and gas drilling operations, TEC is an effective cooling mechanism for instruments. Nevertheless, limitations such as the relatively low energy conversion efficiency and ability to dissipate only a limited amount of heat flux may seriously damage the lifetime and performance of the instrument. Many researches were conducted to expand the efficiency of TEC. The material parameters are the most significant, but they are restricted by currently available materials and module fabricating technologies. Therefore, the main objective of finding the optimal TEC design is to define a set of design parameters. In this paper, technical issues of TEC were discussed. After that, a new method of optimising the dimension of TEC using simulated annealing (SA), to maximise the cooling rate was proposed. Equality constraint and inequality constraint were taken into consideration. This work reveals that SA performs better than genetic algorithm in terms of stability and reliability and found a better geometric design of single-stage TEC which maximise cooling rate when compared with Cheng's (2005) work. Copyright © 2017 Inderscience Enterprises Ltd.